Characterization of Cancer/Testis Antigens as Prognostic Markers of Ovarian Cancer - Ramilia Vlasenkova; Daliya Konysheva; Alsina Nurgalieva; Ramziya Kiyamova (Diagnostics, 2023)
The main goal of this study was to characterize cancer/testis antigens (CTAs) as potential molecular markers of ovarian cancer. First, we gathered and analyzed a significantly large dataset of 21 selected CTAs that are encoded by 32 genes; the dataset consisted of the mutation data, expression data, and survival data of patients with ovarian cancer (n = 15,665). The 19 functionally significant missense mutations were identified in 9 CTA genes: ACRBP, CCT4, KDM5B, MAGEA1, MAGEA4, PIWIL1, PIWIL2, PRAME, and SPA17. The analysis of the mRNA expression levels of 21 CTAs in healthy and tumor ovarian tissue showed an up-regulation in the expression level of AKAP3, MAGEA4, PIWIL1, and PRAME in tumor samples and a down-regulation in the expression level of CTAG1A, CTAG1B, MAGEC1, and PIWIL2. The CCT4 up-regulation and PRAME mutations were correlated with a good prognosis for ovarian cancer, while higher levels of GAGE2A and CT45A1 mRNAs were correlated with a poor prognosis for ovarian cancer patients. Thus, GAGE2, CT45, CCT4, and PRAME cancer/testis antigens can be considered as potential prognostic markers for ovarian tumors, and GAGE2, CCT4, and PRAME were revealed to be correlated with the prognosis for ovarian cancer patients for the first time.